A comprehensive review on the processing-property relationships of laser strengthened magnesium - Alessandro M. Ralls; Aaksheta Agnel; Pradeep L. Menezes (Journal of Magnesium and Alloys, 2024)
Among the existing series of softer metals, magnesium (Mg) has attracted much attention due to its impressive strength-to-weight ratio. However, due to its ease of deformability, Mg tends to suffer from rapid degradation in a wide variety of abrasive and electrochemical environments. One method of improving its surface properties is through surface modification techniques. Among the existing techniques, laser shock peening (LSP) has been one of the most widely utilized processes due to its surface-hardening-like effects. Despite this understanding, a comprehensive review has yet to exist that encapsulates the strengthening mechanism of LSP for Mg and its influence in degradation environments. This review aims to encapsulate the existing research around the LSP field for Mg. Specifically, an understanding of the surface-strengthening effects in relation to its mechanical, tribological, corrosion, and tribo-corrosion characteristics is elucidated. Additionally, the feasibility of LSP for Mg materials in critical industries is also discussed. Through this work, a novel understanding of LSP for Mg can be understood, which can provide a future direction for research in this field.